AKTIVISME NGOS DALAM UPAYA MENGHENTIKAN LYNAS CORPORATION (STUDI KASUS: LYNAS ADVANCED MATERIALS PLANT DI MALAYSIA) - M Faiz Munandar; Den Yealta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research explains how activism efforts of Transnational Advocay Network conducted by several Malaysian local NGOs and international NGOs that seeks to dismiss a proprietary installation project Lynas Corporation in Kuantan, Malaysia. This movement considers that the actions taken by the Government of Malaysia is not appropriate for allowing the operation of one of the Lynas refinery Lynas Advanced Materials Plant (LAMP).Lynas is considered detrimental to the environment and public health around because the radioactive waste produced by the manufacturer. New York Times article also sensitize local communities to stop the LAMP. Local NGOs such as Save Malaysia Stop Lynas and other coalition groups continue to campaign to pressure the government not to grant operating licenses over these companies, they seek to enlist the support of the international community to form a coalition together with international NGOs such as Greenpeace and Friends of the Earth Australia to build up pressure from international community against the Malaysian government to immediately stop the Lynas in Kuantan.Keywords: Transnational Advocacy Network, Non-Govermental Organization, human security, rare-earth, radioactive waste